Using Think Pair Share in Improving Students’ Writing in Descriptive Text - Sitti Nurjannah Hamzah; Andi Nurika Faisal (CV. Eureka Murakabi Abadi, 2021)
The aim of this research is to find out whether the implementation of Think Pair Share is able to improve the students’ writing skill on descriptive text. This research is design through quasi experimental design where the treatment is administered to the experimental and control class. The sampling is taken by using purposive sampling. The instrument used were test and questionnaires. There were several treatments by the implementation of Think Pair Share the test was given in pretest and posttest. The data was analyzed by using SPSS 26 to get the statistics data of the research. The data shows that the result of posttest for experimental class was higher than the result of posttest in control class. The result of paired sample test of experimental and control class for pre-test and posttest which were normally distributed. It means that, there were significance differences between the average values of the student’ pretest and posttest. It was proven by the significance 2 tailed of 0.000 < 0.005. It can be concluded that, the implementation of Think Pair Share can improve the students’ writing ability in descriptive text.